Laboratory model for experimental study of operating parameters of existing installations with batteries, voltage inverter and photovoltaic solar converters - Petrenko, A.; Kruhliak, H.; Lyktei, V.; Ivanchenko, A. (Energy and Automation, 2025)
The article discusses the relevance of developing a laboratory model for the experimental study of the operating parameters of installations with batteries, voltage inverters, and photovoltaic solar converters. Materials and research methods are described, including the use of modern technologies such as microcontrollers with WiFi, analog-to-digital converters, and cloud environments for data storage and analysis. The results of experimental studies are presented, which demonstrate that the correct setting of operating parameters can significantly reduce the load on batteries and voltage inverters, increasing their durability and reducing maintenance costs. The practical application of the research results will help improve the efficiency and reliability of hybrid solar power systems using renewable energy sources.Key words: laboratory model, experimental study, rechargeable battery, voltage inverter, photovoltaic solar converters